Digitalisasi dan Pengambilan Keputusan Manajerial dalam Manajemen Pendidikan Dasar - Nurul Jum'ah Fathi Huballoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of digitalization in managerial decision-making in primary education through a comprehensive literature review. The development of digital technology has brought significant changes to school management practices, particularly in data utilization, administrative efficiency, and evidence-based decision-making. This study employs a qualitative approach using a literature review method. The findings indicate that digitalization supports more effective managerial decision-making through the provision of accurate data, increased transparency, and improved strategic planning in schools. However, the effectiveness of digital-based decision-making is strongly influenced by principals’ digital leadership competencies as well as the readiness of human resources and supporting infrastructure. This study is expected to contribute conceptually to the development of primary education management and serve as a reference for strengthening digital leadership in schools.